2012
DOI: 10.1080/10410236.2011.586990
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Cancer-Related Information From Media and Family/Friends Increases Fruit and Vegetable Consumption Among Cancer Patients

Abstract: Previous research suggests positive effects of health information seeking on prevention behaviors such as diet, exercise and fruit and vegetable consumption among the general population. The current study builds upon this research by examining the effect of cancer patients’ active information seeking from media and (non-medical) interpersonal sources on fruit and vegetable consumption. The results of this longitudinal study are based on data collected from a randomly drawn sample from the Pennsylvania Cancer R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 30 publications
3
58
0
2
Order By: Relevance
“…Overall, our study has shown that health media use is an important mediator both in the education and household income models. Given that the distribution of multiple risk behaviors is not equally distributed, but clustered around specific population groups [4][5][6][7][8], the focus of health promotion efforts should be directed at addressing multiple risk behaviors instead of targeting single risk behaviors one at a time. In this regard, our findings suggest that effective use of health media plays an important role in health promotion among those in low SES.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, our study has shown that health media use is an important mediator both in the education and household income models. Given that the distribution of multiple risk behaviors is not equally distributed, but clustered around specific population groups [4][5][6][7][8], the focus of health promotion efforts should be directed at addressing multiple risk behaviors instead of targeting single risk behaviors one at a time. In this regard, our findings suggest that effective use of health media plays an important role in health promotion among those in low SES.…”
Section: Discussionmentioning
confidence: 99%
“…1 = "less than $5000", 2 = "$5000 to $7499", and so on; Range = [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…Information seeking has also been conceptualized as an active effort to obtain specific information outside of routine patterns of exposure to information from mediated and interpersonal sources (Niederdeppe, Hornik, Kelly et al, 2007; Shim, Kelly, & Hornik, 2006). Information seeking can be an effective behavior to aid in coping with the cancer experience (Case, Andrews, Johnson, & Allard, 2005; Loiselle, Lambert, & Cooke, 2006), help guide decision-making relating to treatment and survivor issues (Gray, Armstrong, DeMichele, Shwartz, & Hornik, 2009; McInnes, Cleary, Stein et al, 2008; Walsh, Trentham-Dietz, Schroepfer et al, 2010), as well as promote the adoption of healthy lifestyle behaviors (Bandura, 1986; Johnson, 1997; Lewis, Martinez, Freres et al, 2012; Ramirez, Freres, Martinez et al, in press).…”
Section: Information Seeking Among Cancer Patientsmentioning
confidence: 99%
“…Recently, health communication scholars have begun to examine how cancer patients achieve fulfillment of their informational needs (Mayer, Terrin, Kreps et al, 2007; Nagler et al, 2010) through actively searching for cancer-related information from family, friends, and mass media sources (Lewis et al, 2012), health care providers (Leadbeater, 2001; Talosig-Garcia & Davis, 2005), as well as actively engaging in information received from their treating physicians and other health professionals (Lewis, Gray, Freres, & Hornik, 2009; Martinez, Schwartz, Freres, Fraze, & Hornik, 2009; Tan, Bourgoin, Gray, Armstrong, & Hornik, 2011). This is an important population to study given the abundance of cancer-related information publicly available in the current media environment (see Ramirez et al, in press).…”
Section: Information Seeking Among Cancer Patientsmentioning
confidence: 99%